2013
DOI: 10.1016/j.nucmedbio.2012.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of backbone-cyclized HER2-binding 2-helix Affibody molecule for In Vivo molecular imaging

Abstract: Evaluation of backbone-cyclized HER2-binding 2-helix Affibody molecule for In Vivo molecular imaging. Nuclear Medicine and Biology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…First, anti-C5b-9 is a biological macromolecule with a large molecular weight, complex structure and immunogenicity and may not be appropriate for use in humans. Recent reports [26,27] have shown that an affibody may be a potential substitute in future studies because affibodies are functionally similar to antibodies but display certain advantages, including a small molecular weight, weak immunogenicity, strong tissue penetration and high affinity. Due to the higher affinity towards specific molecular targets than peptides and smaller size compared to antibodies, affibody molecules are attractive candidates as a promising platform for targeting imaging and therapy applications [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…First, anti-C5b-9 is a biological macromolecule with a large molecular weight, complex structure and immunogenicity and may not be appropriate for use in humans. Recent reports [26,27] have shown that an affibody may be a potential substitute in future studies because affibodies are functionally similar to antibodies but display certain advantages, including a small molecular weight, weak immunogenicity, strong tissue penetration and high affinity. Due to the higher affinity towards specific molecular targets than peptides and smaller size compared to antibodies, affibody molecules are attractive candidates as a promising platform for targeting imaging and therapy applications [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Euthanasia was performed under Ropmpun/Ketalar anesthesia, and all efforts were made to minimize suffering. 68 Ga and 111 In labeled conjugates were compared using a dual label study was performed to improve the statistical power and to minimize the number of tumor-bearing animals, as it was described by Honarvar and co-workers [29].…”
Section: Methodsmentioning
confidence: 99%
“…The resulting destabilization was partially compensated by stabilizing mutations and disulfide bonding [21,22]. The two-helix affibody has only been able to achieve low nanomolar affinity to date [21].…”
Section: Protein-based Molecular Imaging Agentsmentioning
confidence: 99%
“…The resulting destabilization was partially compensated by stabilizing mutations and disulfide bonding [21,22]. The two-helix affibody has only been able to achieve low nanomolar affinity to date [21]. The two-helix affibody has been applied to molecular imaging in HER2-expressing tumor xenograft models successfully when labeled with 68 Ga [23], 18 F [24], and 111 In [25].…”
Section: Protein-based Molecular Imaging Agentsmentioning
confidence: 99%